KONTRIBUSI HUKUM ADAT DALAM PEMBANGUNAN HUKUM NASIONAL - Ni Luh Gede Hadriani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The development of legal substance and structure in our country is not optimal at dy- namics of social and cultural life. By looking at these conditions, the contribution of Customary Law in development of National Law really needs to be initiated, studied and developed. Laws should be built in line with the socio-cultural structure of our own nation. Through that custom- ary law will be able to contribute to the development of National Law. There is three contribu- tion to the development, the first is contribution of legal stability, contribution of legal structure, and the contribution of legal culture.